PENGARUH LINGKUNGAN KERJA DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT. PLN (PERSERO) UPDK PEKANBARU - Ningsi, Jesika Aprillia; Suryalena, Suryalena (Jurnal Daya Saing, 2024)
This research aims to determine and analyze the influence of the work environment and competence on employee performance at PT. PLN (Persero) UPDK Pekanbaru. This study had 48 respondents who were total employees at PT. PLN (Persero) UPDK Pekanbaru. This research uses a Census sampling technique or Total Sampling. This research uses validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression, t tests, F tests, and coefficient of determination tests (R2). The results of this research show that the work environment and competence have a significant effect on employee performance at PT PLN (Persero) UPDK Pekanbaru. Keywords: Work environment, competency, employee performance